Experimental Analyses of Different PVT Collector Designs for Heating and Cooling Applications in Buildings. (November 2015) - Cremers, Jan; Mitina, Irina; Palla, Nansi; Klotz, Fritz; Jobard, Xavier; Eicker, Ursula
Abstract: The experimental results of two differently designed hybrid PVT (photovoltaic-thermal) collectors are reported in the present paper. As well both collectors are being tested on an outdoor test stand varying the inlet temperature and the mounting solutions. The focus of the conducted experiments lay on comparing the performance of PVT collectors with and without backside shielding in order to understand which building integration options for different applications (heating or cooling) are optimal. The results demonstrate that for both heating and cooling applications the shielding of PVT collector leads to improving of the collector efficiency by 20-30%.